Symptom clusters in newly diagnosed glioma patients: which symptom clusters are independently associated with functioning and global health status? - Coomans, Marijke; Wick, Wolfgang (Neuro-Oncology, 2019)
AbstractBackground. Symptom management in glioma patients remains challenging, as patients suffer from various concurrently occurring symptoms. This study aime
Gesehen am 13.02.2020